A Correlational Study to Assess the Knowledge and Practices Regarding Central Line-Associated Bloodstream Infection Care Bundle among the Staff Nurses in Selected Hospitals of Maharashtra in View to Prepare the Multi Modular Learning Tool - Veer, Nilesh; Sharma, Jyoti (International Journal of Nursing Research, 2023)
The aim of this research is to assess the level of knowledge held by staff nurses in relation to the central line-associated bloodstream infection care bundle as well as their actions. The investigator chose to use a descriptive survey approach with descriptive study design and to investigate the staff nurses’ knowledge of and behaviors relating to the central line-related bloodstream infection treatment package. The sample consisted of 125 registered nurses who were working in the intensive care unit of the hospital. For this investigation, a non-probability purposeful sampling strategy was utilized to select the sample. The analysis of the information included both descriptive and inferential statistical methods. The Karl Pearson correlation coefficient test and the Chi-square test used to refer to examine the correlation and determine the relationship between knowledge and practice about the treatment of bloodstream infections linked with central lines and demographic factors. The findings of this investigation demonstrated that 79 (63.2%) had inadequate knowledge followed by 38 (30.4%) had moderate knowledge and 8 (6.4%) had adequate knowledge regarding central line-associated bloodstream infection (CLABSI) care bundle. Seventy-five (60%) had poor level of practices, 40 (32%) had average level of practices, and 10 (8%) had good level of practices regarding CLABSI care bundle, there is positive correlation that was identified between knowledge and practices, that is, (r = 0.7501). According to the results of this investigation, staff nurses had knowledge and practices about the care bundle for central line-related bloodstream infections that were on average appropriate. Investigator recommends that the distribution of the multi modular learning tool addressing the central line-related bloodstream infections care bundle, both the knowledge, and the practices will be enhanced.